A comparative study in descriptions of coupled kinematic hardening rules and ratcheting assessment over asymmetric stress cycles. Issue 6 (9th November 2016) - Varvani‐Farahani, A
Abstract: The present study evaluates coupled kinematic hardening rules at which the calculation of plastic moduli is coupled with these models through the consistency condition of yield surfaces. The frameworks of the Ohno–Wang (O–W), McDowell, Jiang–Sehitoglu (J–S), Chen–Jiao–Kim (C–J–K) and Ahmadzadeh–Varvani (A–V) hardening rules and their incorporated dynamic recovery terms/coefficients were discussed for steel samples undergoing asymmetric stress cycles. Different hardening rules offered distinct procedures to determine terms/coefficients and to generalize hardening rule descriptions applicable for different materials and loading spectra. The progressive evolution of backstress over plastic deformation was attributed to the interaction of dislocations controlled by the dynamic recovery of the models. The predicted ratcheting curves through the C–J–K and A–V hardening rules closely agreed with ratcheting data of 1045 and 304 steel samples tested at different loading paths. The O–W, J–S and McDowell hardening rules showed some overprediction in ratcheting as compared with experimental data.